β-Arrestin 1 and 2 similarly influence μ-opioid receptor mobility and distinctly modulate adenylyl cyclase activity - Markova, Vendula; Hejnova, Lucie; Benda, Ales; Novotny, Jiri; Melkes, Barbora (Cellular signalling, 2021)
β-Arrestins are known to play a crucial role in GPCR-mediated transmembrane signaling processes. However, there are still many unanswered questions, especially those concerning the presumed similarities and differences of β-arrestin isoforms. Here, we examined the roles of β-arrestin 1 and β-arrestin 2 at different levels of μ-opioid receptor (MOR)-regulated signaling, including MOR mobility, internalization of MORs, and adenylyl cyclase (AC) activity. For this purpose, naïve HEK293 cells or HEK293 cells stably expressing YFP-tagged MOR were transfected with appropriate siRNAs to block in a specific way the expression of β-arrestin 1 or β-arrestin 2. We did not find any significant differences in the ability of β-arrestin isoforms to influence the lateral mobility of MORs in the plasma membrane. Using FRAP and line-scan FCS, we observed that knockdown of both β-arrestins similarly increased MOR lateral mobility and diminished the ability of DAMGO and endomorphin-2, respectively, to enhance and slow down receptor diffusion kinetics. However, β-arrestin 1 and β-arrestin 2 diversely affected the process of agonist-induced MOR endocytosis and exhibited distinct modulatory effects on AC function. Knockdown of β-arrestin 1, in contrast to β-arrestin 2, more effectively suppressed forskolin-stimulated AC activity and prevented the ability of activated-MORs to inhibit the enzyme activity. Moreover, we have demonstrated for the first time that β-arrestin 1, and partially β-arrestin 2, may somehow interact with AC and that this interaction is strongly supported by the enzyme activation. These data provide new insights into the functioning of β-arrestin isoforms and their distinct roles in GPCR-mediated signaling.
Keywords: HEK293 buňky; beta arrestin 1; receptory opiátové mu; Adenylyl Cyclases; beta-Arrestin 1; lidé; Receptors, Opioid, mu; beta arrestin 2; beta-Arrestin 2; adenylátcyklasy; beta arrestiny; HEK293 Cells; beta-Arrestins; Humans